LANGUAGE DISORDERS IN INDIVIDUALS WITH CEREBRAL PALSY AT SAYAP IBU BINTARO FOUNDATION: A CASE STUDY OF A 25-YEAR-OLD - Bagus Triadi, Rai; Adella, Adella; Muhammad Nur, Adam (Jurnal Kata, 2025)
Language development is a gradual process in acquiring the ability to understand and use language for communication. This process involves biological, cognitive, social, and environmental aspects. In relation to biological and cognitive aspects, individuals with cerebral palsy experience difficulties in the stages of language development. Therefore, this study aims to describe language disorders in a 25-year-old individual with cerebral palsy at the Sayap Ibu Bintaro Foundation. These language disorders are specifically examined in the phonological domain. This study employs a qualitative method with a case study approach, based on the assumption that individuals with special needs, such as cerebral palsy, possess unique characteristics that are not generalizable. The findings reveal the presence of phonological disorders, including phoneme deletion, consonant substitution, simplification of consonant clusters into the nasal sound /ŋ/, and the addition of certain sounds. These disorders are caused by limitations in the motor control of speech organs, which are associated with the subject’s neurological condition. The results of this study are expected to provide recommendations for phonological therapy patterns for individuals with cerebral palsy who experience similar language disorders.